2004
DOI: 10.2116/analsci.20.351
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Refractory Elements in Used Lubricating Oil by ICPOES Employing Emulsified Sample Introduction and Calibration with Inorganic Standards

Abstract: The quantitative determination of wear metals in used lubricating oil is an important application for engine and turbine diagnostic purposes, allowing preventive maintenance (oil changes, equipment overhauls and replacement of components) to be made before the collapse of equipment. 1 The wearing of metals causes solid metal debris of different sizes, metal oxides and metallorganic species, from mechanical wear, oxidative corrosion and chemical corrosion, respectivery. 1-3Several analytical methodologies based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…Moreover, severe matrix interferences have already been observed during the analysis of organic solutions in ICP-OES due to plasma interactions (Botto, 1987). In order to minimize these problems, five solutions are globally described in the literature with organic injection using micro-nebulisation system (Dreyfus et al, 2005;Botto, 2002), desolvatation using ultrasonic nebulisation and membrane (Botto and Zhu, 1996;Duyck et al, 2002), digestion of the sample (Wondimu et al, 2000;Heilmann et al, 2004, Lopez andMonaco, 2004), microemulsion (Souza et al, 2004;Wang et al, 2003) for introduction of an aqueous phase in the plasma and finally electrothermal vaporization (Resano et al, 2001;Saint'Pierre et al, 2002). Micronebulization and ultrasonic nebulisation are sometimes used in combination with oxygen addition into the plasma, which is particularly recommended with ICP-MS detection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, severe matrix interferences have already been observed during the analysis of organic solutions in ICP-OES due to plasma interactions (Botto, 1987). In order to minimize these problems, five solutions are globally described in the literature with organic injection using micro-nebulisation system (Dreyfus et al, 2005;Botto, 2002), desolvatation using ultrasonic nebulisation and membrane (Botto and Zhu, 1996;Duyck et al, 2002), digestion of the sample (Wondimu et al, 2000;Heilmann et al, 2004, Lopez andMonaco, 2004), microemulsion (Souza et al, 2004;Wang et al, 2003) for introduction of an aqueous phase in the plasma and finally electrothermal vaporization (Resano et al, 2001;Saint'Pierre et al, 2002). Micronebulization and ultrasonic nebulisation are sometimes used in combination with oxygen addition into the plasma, which is particularly recommended with ICP-MS detection.…”
Section: Introductionmentioning
confidence: 99%
“…ICP-OES [10][11][12][13] offers the possibility to simultaneously measure almost all metals and some non-metals. Hence, its productivity in the analysis of a large amount of samples is superior to FAAS.…”
Section: Introductionmentioning
confidence: 99%
“…The emulsification method adopted in the present study was followed from the reported method [15] with a slight modifications in order to analyse the multi-elements present in the lubricating grease samples. This method was carried out with the addition of Triton X-100, which gave acceptable recoveries and stability in emulsion [16]. However to improve the percentage of recovery, Triton X-100 concentration was varied in the range of 1-10 %.…”
Section: Resultsmentioning
confidence: 99%